2004
DOI: 10.1242/jcs.01226
|View full text |Cite
|
Sign up to set email alerts
|

KIN17 encodes an RNA-binding protein and is expressed during mouse spermatogenesis

Abstract: Genotoxic agents deform DNA structure thus eliciting a complex genetic response allowing recovery and cell survival. The Kin17 gene is up-regulated during this response. This gene encodes a conserved nuclear protein that shares a DNA-binding domain with the bacterial RecA protein. The KIN17 protein binds DNA and displays enhanced expression levels in proliferating cultured cells, suggesting a role in nuclear metabolism. We investigated this by studying the expression profile of KIN17 protein during mouse sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 64 publications
(82 reference statements)
2
26
0
Order By: Relevance
“…Thus, the C-terminal domain of hKIN17 has structural similarity with various SH3-like domains, even if it lacks similarities in either primary sequence or charge distribution. The C-terminal domain of hKIN17 binds RNA in vitro Since hKIN17 protein is able to recognize RNA homopolymers and can bind RNA in vivo, 16 we investigated which region(s) of the protein interact(s) with RNA. Three constructs containing either the Nterminal globular region 1-160 (shown to be folded by NMR analysis; data not shown), the same region without the zinc finger 68-160 (shown to be folded by NMR analysis), 24 or the C-terminal domain 268-393 described here were tested for their ability to bind RNA using the same 32 P-labelled RNA probe as that used to characterize the RNA interaction properties of the full-length hKIN17.…”
Section: -Like Subdomainsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the C-terminal domain of hKIN17 has structural similarity with various SH3-like domains, even if it lacks similarities in either primary sequence or charge distribution. The C-terminal domain of hKIN17 binds RNA in vitro Since hKIN17 protein is able to recognize RNA homopolymers and can bind RNA in vivo, 16 we investigated which region(s) of the protein interact(s) with RNA. Three constructs containing either the Nterminal globular region 1-160 (shown to be folded by NMR analysis; data not shown), the same region without the zinc finger 68-160 (shown to be folded by NMR analysis), 24 or the C-terminal domain 268-393 described here were tested for their ability to bind RNA using the same 32 P-labelled RNA probe as that used to characterize the RNA interaction properties of the full-length hKIN17.…”
Section: -Like Subdomainsmentioning
confidence: 99%
“…Three constructs containing either the Nterminal globular region 1-160 (shown to be folded by NMR analysis; data not shown), the same region without the zinc finger 68-160 (shown to be folded by NMR analysis), 24 or the C-terminal domain 268-393 described here were tested for their ability to bind RNA using the same 32 P-labelled RNA probe as that used to characterize the RNA interaction properties of the full-length hKIN17. 16 The Northwestern analysis showed that the N-terminal domain comprising the zinc finger interacts efficiently with RNA in vitro, and that the deletion of the zinc finger from this domain drastically reduces RNA binding ( Figure 3). The C-terminal domain showed an intermediate RNA-binding activity.…”
Section: -Like Subdomainsmentioning
confidence: 99%
See 3 more Smart Citations